2016
DOI: 10.1371/journal.pone.0153899
|View full text |Cite
|
Sign up to set email alerts
|

Marked Rise in the Prevalence of Asymptomatic Plasmodium falciparum Infection in Rural Gabon

Abstract: Control strategies implemented a decade ago led to a marked reduction in the prevalence of malaria in many countries. In Dienga, southeastern Gabon, the prevalence of microscopic P. falciparum infection was 7% in 2003, close to the pre-elimination threshold of 5%. The aim of this work was to determine the prevalence of P. falciparum infection in the same community a decade later. A cohort of 370 individuals aged from 3 to 85 years living in Dienga was investigated for P. falciparum infection; during six passag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 43 publications
(58 reference statements)
5
21
2
Order By: Relevance
“…The prevalence of asymptomatic P. falciparum infections by microscopy differed between the age groups surveyed, gradually increasing during childhood and then declining from late adolescences into adulthood. This age-dependent trend in microscopic prevalence was in agreement with previous studies [42][43][44] and was observed at the end of the wet and dry seasons across both catchment areas in BD. These results indicate the importance of understanding the burden of disease and consequences of asymptomatic malaria in the adolescent population, which have traditionally been neglected and rarely targeted for malaria control.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of asymptomatic P. falciparum infections by microscopy differed between the age groups surveyed, gradually increasing during childhood and then declining from late adolescences into adulthood. This age-dependent trend in microscopic prevalence was in agreement with previous studies [42][43][44] and was observed at the end of the wet and dry seasons across both catchment areas in BD. These results indicate the importance of understanding the burden of disease and consequences of asymptomatic malaria in the adolescent population, which have traditionally been neglected and rarely targeted for malaria control.…”
Section: Discussionsupporting
confidence: 92%
“…14,33,53 Recent findings from an area with intense seasonal malaria in Burkina Faso suggests that submicroscopic parasite carriers are an important source of onward transmission, particularly at the end of the dry season, and are responsible for about half of the infectious P. falciparum reservoir. 4 Although our results are similar to previous studies and demonstrate that asymptomatic infections made up a substantial portion of the P. falciparum reservoir across all ages, 42,44,48,54 their ability to produce mature gametocytes and transmit remains vague based on the microscopy results. Further work to evaluate the potential contribution of these asymptomatic infections for onward transmission needs to be assessed and monitored using more sensitive methods if we are to implement appropriate elimination strategies in BD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In Dienga, the prevalence of P. falciparum infection decreased around 2003 [30] but a decade after this prevalence rose markedly [29]. This situation may be associated with a lack of ongoing efforts to fight against the disease (ie local anti-malarial drug use, prevention measures).…”
Section: Discussionmentioning
confidence: 99%
“…From April 2013 to June 2014, through six field missions, a cohort composed of 370 indiduals was followed to investigate P. falciparum infection [29]. The participants were composed of volunteers permanently living in Dienga; primary school children (≥ 3 years) and adults.…”
Section: Study Population and Biological Samplesmentioning
confidence: 99%